2010
DOI: 10.1029/2009jc005804
|View full text |Cite
|
Sign up to set email alerts
|

Spring of no Kuroshio intrusion in the southern Taiwan Strait

Abstract: The Taiwan Strait connects the East China Sea (ECS) to the South China Sea (SCS). Typically, in spring, the water in the SCS and a branch of the Kuroshio occupy the eastern part of the strait while the China coastal waters, including a large contribution from the Changjiang (Yangtze River), occupy the western part. During spring 2008, when the Taiwan Strait was under the influence of La Niña, and according to field observations, the Kuroshio branch did not contribute much to the waters in the southern Taiwan S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
6
27
0
2
Order By: Relevance
“…The model-derived velocity structure exhibited two segments: one was the southward CCC, which was confined in a narrow zone hugging the west coast of the TWS; the other was the northward flowing Taiwan Strait Warm Current located in the rest of the TWS. Such a pattern was consistent with previous results from in situ observations, supporting the validity of our numerical model (Fu et al, 1991;Liang et al, 2003;Chen et al, 2010).…”
Section: Model Verification and Model Resultssupporting
confidence: 82%
“…The model-derived velocity structure exhibited two segments: one was the southward CCC, which was confined in a narrow zone hugging the west coast of the TWS; the other was the northward flowing Taiwan Strait Warm Current located in the rest of the TWS. Such a pattern was consistent with previous results from in situ observations, supporting the validity of our numerical model (Fu et al, 1991;Liang et al, 2003;Chen et al, 2010).…”
Section: Model Verification and Model Resultssupporting
confidence: 82%
“…After wind speed weakening, the SST around the Penghu Islands rose immediately, which agrees with the sequence of SST maps shown in Fig. 10d-f previous studies; e.g., Chen et al 2010;Liao et al 2013;Lee et al 2014). Through the application of the warning mechanism, the hindcast of the 2008 winter showed that a high-risk warning could precede the coldest water day by 19 days (Fig.…”
Section: Hindcasting Cold Water Dayssupporting
confidence: 74%
“…Chang et al (2009) used satellite SST images around the Penghu Islands to show that the minimum SST (12.6 °C) in February 2008 was lower than the February climatological temperature (20 °C). The strong northeast monsoon in the winter of 2008, associated with La Niña, may drive the cold China Coastal Current to intrude more southward into the southern TS and can even suppress the northward warm Kuroshio Branch Current intruding the TS (Chen et al 2010;Lee et 25 al. 2014).…”
mentioning
confidence: 99%
“…The metal concentrations at some sites of 20 to 28 were generally in the higher parts of the ranges of metal concentrations recorded in this study. This might be owing to the pollution from western Taiwan as the flows are generally northward (Jan et al 2002(Jan et al , 2006Chen and Sheu 2006;Chen et al 2010). Furthermore, southwardflowing China coastal currents frequently turn towards the east near 26°N (Jan et al 2002(Jan et al , 2006He et al 2014), and this is probably another reason.…”
Section: Metals In Total Concentrationsmentioning
confidence: 99%